A verticalização em cidades médias : uma análise da cidade de Rondonópolis-MT - Melo, Josenilton Balbino de (2013)
This research comes to dealing with the process of (re) production of urban space in the city of Rondonópolis-MT, emphasizing the process of vertical buildings as a major shapers of this urban space, aiming at modernizing the look but also the aspect of segregating space. The research aims to analyze the process of vertical integration of the buildings in the city of Rondonópolis-MT, spatializing the vertical constructions in the urban city. For this it was necessary to understand economic development and urban expansion that the city has suffered and is suffering over the years. This factor can be explained from the year 1947, as the city is included in the context of capitalist production, and more recently from the arrival and deployment of various agricultural industries in the county.